Impact of Equine Chorionic Gonadotropin Associated with Temporary Weaning, Estradiol Benzoate, or Estradiol Cypionate on Timed Artificial Insemination in Primiparous Bos Indicus Cows - Souza,Andre Luis Bastos (2016)
The study aimed to determine the impact of equine chorionic gonadotropin (eCG) associated with different timed artificial insemination (TAI) protocols on the pregnancy rate (PR) in Bos indicus cows previously treated with progesterone. Five hundred and fifty-seven primiparous cows were subjected to the following treatments: on day 0 (d0), GeCGTW (group equine Chorionic Gonadotropin+Temporary Weaning;n=178) received 0,558 g intravaginal progesterone (P4)+1.0 mg of estradiol benzoate (EB) (IM); on d8 (P4 removal+0,075 mg D-cloprostenol + 400 IU eCG + TW for 48 h); on d10, TAI + calves return to dam; GeCGEB (group equine Chorionic Gonadotropin+Estradiol benzoate; n=176) the same as GeCGTW without TW + application of 1.0 mg of EB on d9; GeCGEC (group equine Chorionic Gonadotropin+Estradiol Cypionate; n=203), the same as GeCGTW without TW+1.5 mg EC (IM). On d35, post TAI, pregnancy diagnosis (PD) was performed. Non-pregnant animals remained under clean-up bulls for 90 days. After this period, the animals were subjected to PD using ultrasound. The PR of TAI was 51.1%, 47.1%, and 47.8% for GeCGTW, GeCGEB24, and GeCGEC (P>0.05) respectively. The PR under clean-up bulls was 88.3%, 47.3%, and 31.1% (P<0.05). The final PR (TAI+clean-up bulls) of the groups was 94.4%, 72.1%, and 64.0%, respectively (P<0.05). It was concluded that no differences in PR among the protocols related to TAI were detected; PR in the GeCGTW protocol under clean-up bulls was higher compared to others (P<0.05); the overall PR of cows subjected to TAI+clean-up bulls was significantly higher in GeCGTW than in the other groups.